Lets hear it for dusty, musty, and fusty: Rediscovering good government - Henry, Nicholas (2013)
The New Public Management is public administration's latest iteration about what it should be doing. The New Public Management promotes many good ends, but the price of these benefits may be one of overlooking or disregarding some old-fashioned fundamentals, notably governmental honesty and competency. Examples of these oversights are given in the context of contemporary political corruption and governmental incompetence. A case is made for rediscovering public administration's mission of yesteryear, Good Government. - Reproduced.
Keywords: God governance; Public administration